REVITALISASI KAMPUNG NELAYAN CILINCING - Nicholas Aries; Rudy Surya (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The issue of decreasing living quality happens in most coastal villages in Indonesia. One of them is Cilincing fishermen's village located in North Jakarta. Cilincing fishermen's village is a village that grows organically without any proper planning. This condition helps worsen the issue of living quality caused by humans and nature. The low living quality at Cilincing fishermen's village showed it is an unhabitable territory, especially in long-term conditions. It is also a form of displaying how people with low income live their life. The idea of relocating will be a new challenge to be done so that to be able to get around the new development needs to be done. The new development is a method to achieve revitalization without relocating the inhabitants henceforth, able to preserve to locality aspect of the environment.  The main idea of the revitalization program that uses a new development method is to provide a habitable living facility, especially for the native inhabitants of Cilincing fishermen's village, followed by a secondary program of facilities and infrastructure that function to help the activities of the inhabitants. The output of the revitalization program is vertical housing with adaptive characteristics without getting rid of the local aspects. In hopes of increasing the living quality of Cilincing fishermen's village inhabitants. As well as providing infrastructure and facilities which can increase the fishermen's village economic condition. Keywords: Cilincing; fishermen’s village; living quality; new development AbtrakAdanya fenomena penurunan kualitas berhuni yang terjadi di mayoritas kampung nelayan di Indonesia salah satunya merupakan Kampung Nelayan Cilincing yang terletak di Jakarta utara. Kampung Nelayan Cilincing merupakan kawasan desa pesisir yang terbentuk secara organik dan bertumbuh dengan pesat tanpa adanya proses perencanaan, hal ini menimbulkan berbagai macam masalah yang memengaruhi kualitas berhuni masyarakat di kawasan tersebut baik yang disebabkan oleh manusia maupun alam. Rendahnya kualitas berhuni menunjukkan ketidaklayakan kawasan untuk dihuni dalam jangka waktu yang panjang serta memberikan gambaran kehidupan mayoritas masyarakat dengan penghasilan rendah. Untuk itu dengan dilakukannya relokasi akan menjadi sebuah tantangan tersendiri, agar mampu menyiasati hal tersebut akan dilakukannya sebuah pengembangan baru atau new development. Pengembangan baru merupakan metode untuk melakukan revitalisasi di kawasan kampung nelayan Cilincing tanpa melakukan relokasi penduduk untuk menjaga aspek lokalitas kawasan tersebut. Dengan Ide program utama revitalisasi kawasan adalah menghadirkan fasilitas hunian yang layak huni bagi warga lokal kampung nelayan, didukung oleh program sarana dan prasarana kebutuhan aktivitas warga kampung nelayan Cilincing. Dengan program menyediakan sebuah fasilitas hunian vertikal dengan sifat adapatif tanpa menghilangkan aspek lokalitas yang sudah ada diharapkan dapat meningkatkan kondisi kualitas berhuni masyarakat kampung nelayan. Usulan berupa dukungan prasarana maupun sarana kegiatan yang juga dapat menaikkan kondisi ekonomi di kampung nelayan.